Indoor exposure to airborne polycyclic aromatic hydrocarbons: A comparison of stir bar sorptive extraction and pump sampling. Issue 12 (5th May 2021) - Becker, Roland; Heyn, Lisa; Jung, Christian
Abstract: Stir bar sorptive extraction (SBSE) was compared with standardized pump sampling regarding the prospects to assess airborne levels of polycyclic aromatic hydrocarbons (PAHs) in indoor environments. A historic railway water tower, which will be preserved as a technical monument for museum purposes, was sampled with both approaches because the built‐in insulation material was suspected to release PAHs to the indoor air. The 16 PAHs on the US EPA list were quantified using gas chromatography with mass spectrometric detection in filters from pump sampling after solvent extraction and on SBSE devices after thermal desorption. SBSE was seen to sample detectable PAH masses with excellent repeatability and a congener pattern largely similar to that observed with pump sampling. Congener patterns were however significantly different from that in the PAH source because release from the insulation material is largely triggered by the respective congener vapor pressures. Absolute masses in the ng range sampled by SBSE corresponded to airborne concentrations in the ng L −1 range determined by pump sampling. Principle differences between SBSE and pump sampling as well as prospects of SBSE as cost‐effective and versatile complement of pump sampling are discussed. Abstract : Stir bar sorptive extraction (SBSE) was compared with classical pump sampling for the determination of the airborne levels of 16 polycyclic aromatic hydrocarbons (PAH) on a historic industrial monument that is developed as technical museum for visitors. It was seen that SBSE observed absolute PAH congener masses in the ng range which corresponded to airborne concentrations in the ng L −1 range as determined by pump sampling. Thus, SBSE provides a rapid orientation to assess the necessity for the more complex pump sampling.